To find the equation of the line in slope-intercept form, we need to determine both the slope and the y-intercept.
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (0,4) and (1,8):
m = (8 - 4) / (1 - 0)
m = 4 / 1
m = 4
Now that we have the slope (m = 4), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0,4):
4 = 4(0) + b
4 = 0 + b
b = 4
Therefore, the y-intercept (b) is 4.
Now we can write the equation in slope-intercept form:
y = 4x + 4
derive the equation of the line in slope-intercept from
(0,4) and (1,8)
17 answers
write the equation of the line in slope-intercept from
(0,2) and (1, -1)
(0,2) and (1, -1)
To find the equation of the line in slope-intercept form, we need to determine both the slope and the y-intercept.
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (0,2) and (1, -1):
m = (-1 - 2) / (1 - 0)
m = -3 / 1
m = -3
Now that we have the slope (m = -3), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0,2):
2 = -3(0) + b
2 = 0 + b
b = 2
Therefore, the y-intercept (b) is 2.
Now we can write the equation in slope-intercept form:
y = -3x + 2
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (0,2) and (1, -1):
m = (-1 - 2) / (1 - 0)
m = -3 / 1
m = -3
Now that we have the slope (m = -3), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0,2):
2 = -3(0) + b
2 = 0 + b
b = 2
Therefore, the y-intercept (b) is 2.
Now we can write the equation in slope-intercept form:
y = -3x + 2
write the equation of the line in slope-intercept from
(3,0) and (0,-2)
(3,0) and (0,-2)
To find the equation of the line in slope-intercept form, we need to determine both the slope and the y-intercept.
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (3, 0) and (0, -2):
m = (-2 - 0) / (0 - 3)
m = -2 / -3
m = 2/3
Now that we have the slope (m = 2/3), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (3, 0):
0 = (2/3)(3) + b
0 = 2 + b
b = -2
Therefore, the y-intercept (b) is -2.
Now we can write the equation in slope-intercept form:
y = (2/3)x - 2
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (3, 0) and (0, -2):
m = (-2 - 0) / (0 - 3)
m = -2 / -3
m = 2/3
Now that we have the slope (m = 2/3), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (3, 0):
0 = (2/3)(3) + b
0 = 2 + b
b = -2
Therefore, the y-intercept (b) is -2.
Now we can write the equation in slope-intercept form:
y = (2/3)x - 2
given the equation y=2x + 2, what is the slope? write your answer as an integer
the slope is ____.
the slope is ____.
The slope of the equation y = 2x + 2 is 2.
given the equation y=-2x + 2, what is the slope? write your answer as an integer
the slope is ____.
the slope is ____.
The slope of the equation y = -2x + 2 is -2.
given the equation y=3/4x - 2, what is the y-intercept? write your answer as an ordered pair
the y-intercept is ____.
the y-intercept is ____.
The y-intercept of the equation y = (3/4)x - 2 is (0, -2).
derive the equation of the line in slope-intercept from
(1,-1) and (0,-4)
(1,-1) and (0,-4)
To find the equation of the line in slope-intercept form, we need to determine both the slope and the y-intercept.
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (1, -1) and (0, -4):
m = (-4 - -1) / (0 - 1)
m = (-4 + 1) / (0 - 1)
m = -3 / -1
m = 3
Now that we have the slope (m = 3), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0, -4):
-4 = 3(0) + b
-4 = 0 + b
b = -4
Therefore, the y-intercept (b) is -4.
Now we can write the equation in slope-intercept form:
y = 3x - 4
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (1, -1) and (0, -4):
m = (-4 - -1) / (0 - 1)
m = (-4 + 1) / (0 - 1)
m = -3 / -1
m = 3
Now that we have the slope (m = 3), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0, -4):
-4 = 3(0) + b
-4 = 0 + b
b = -4
Therefore, the y-intercept (b) is -4.
Now we can write the equation in slope-intercept form:
y = 3x - 4
write the equation of the line in slope-intercept from
(0,1) and (1,-4)
(0,1) and (1,-4)
To find the equation of the line in slope-intercept form, we need to determine both the slope and the y-intercept.
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (0, 1) and (1, -4):
m = (-4 - 1) / (1 - 0)
m = -5 / 1
m = -5
Now that we have the slope (m = -5), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0, 1):
1 = -5(0) + b
1 = 0 + b
b = 1
Therefore, the y-intercept (b) is 1.
Now we can write the equation in slope-intercept form:
y = -5x + 1
First, let's find the slope (m) using the formula:
m = (y2 - y1) / (x2 - x1)
Using the points (0, 1) and (1, -4):
m = (-4 - 1) / (1 - 0)
m = -5 / 1
m = -5
Now that we have the slope (m = -5), we can use the slope-intercept form of a line, which is y = mx + b, where m is the slope and b is the y-intercept.
To find the y-intercept (b), we can use one of the points on the line. Let's use (0, 1):
1 = -5(0) + b
1 = 0 + b
b = 1
Therefore, the y-intercept (b) is 1.
Now we can write the equation in slope-intercept form:
y = -5x + 1
the liner equation for y=-3x+2
The equation y = -3x + 2 is already in slope-intercept form, where the slope (m) is -3 and the y-intercept (b) is 2.